A Rare Case of Flare-Up of PID in Infertility Treatment - Leena Wadhwa; Sanjana N. Wadhwa; Sunita Jindal (Hindawi Limited, 2015)
Case Presentation. Mrs. X, 35 years old, case of primary infertility, was diagnosed to have genital tuberculosis on the basis of PCR positive and hysterolaparoscopy findings and received category I ATT for 6 months. Following ATT completion, her USG revealed no evidence of tuboovarian mass or hydrosalpinx. Since her tubes were patent, she underwent 3 cycles of ovulation induction and 2 cycles of IUI. The women presented with acute PID, five days after IUI, and was conservatively managed. She again presented 24 days after IUI with persistent low grade fever and abdominal pain. Suspecting relapse of genital tuberculosis, she was started on category II ATT. She had acute episodes of high grade fever with chills 2 weeks after starting ATT and MRI revealed bilateral TO masses suggestive of pyosalpinx. Emergency laparotomy was done, pus was drained, and cyst wall was removed and HPE was suggestive of chronic inflammation with few granulation tissues. ATT was continued for one year and the woman improved. Conclusion. The possibility of flare-up of PID (pelvic inflammatory disease) in treated case of tuberculosis undergoing infertility management should be kept in mind and aggressive management should be done.